Broadening the urban sustainable energy diapason through energy recovery from waste: A feasibility study for the capital of Serbia. (March 2017) - Nikolic, Ana; Mikic, Miljan; Naunovic, Zorana
Abstract: Metropolitan areas are large consumers of energy and there is a growing need to broaden the urban sustainable energy diapason and increase the share of renewable and sustainable energy in overall energy consumption. This is especially important in countries such as Serbia that have limited domestic fossil fuel resources and rely on energy imports, from the environmental, financial and energy security points of view. In the Serbian capital of Belgrade electricity is produced in coal-fired power plants that have been shown to be vulnerable to flooding and the district heating system is reliant on imported natural gas. The objective of this work was to perform a feasibility study of a combined heat and power municipal solid waste mass burn incineration facility in Belgrade. The feasibility study included a financial and an economic analysis. The City of Belgrade has a developed district heating system and locating the incineration facility next to an existing heating plant would enable the utilization of the heat energy produced by incineration and substitution of a portion of the imported natural gas currently used for district heating. The contributions of energy derived from waste incineration to the total energy consumption in Belgrade were also evaluated. The feasibility study showed that municipal solid waste incineration would be financially and economically positive and viable.